Influence of emotional intelligence on the clinical ability of nursing interns: a structural equation model - Shuangting Dou; Chenyan Han; Conghong Li; Xiaoxin Liu; Wanling Gan (BMC, 2022)
Abstract Background Internship is a critical period during which nursing students develop clinical skills and establish professional attitudes. Requirements for nursing interns are evolving with the development of medicine and the transformation of teaching models. The emotional intelligence (EI) of nursing students has an influence on their clinical performance. This study aimed to investigate the impact of EI on the clinical ability of nursing interns. Methods A cross-sectional observational study was designed to include nursing students interning in a tertiary hospital in Shanghai, China from April 1, 2019 to April 30, 2020 (N = 310). Chinese versions of the EI scale (EIS) and holistic clinical assessment tool (HCAT) were used to measure the EI and clinical ability of interns, respectively. Pearson's correlation coefficient was utilized to determine the correlation between EI and clinical ability. Multiple linear regression analysis was performed to further explore the influence of EI on clinical ability, and the structural equation model (SEM) was used for multivariate path analysis. Results The mean EI and clinical ability scores of interns were 125.17 ± 14.98 and 97.91 ± 19.55, respectively, indicating an upper-moderate level in both aspects. EI scores were correlated positively with clinical ability ones (R = 0.534, p < 0.05). Multivariate path analysis showed that "managing emotions" and "facilitating thought" of EI branches have direct effects on clinical ability. Furthermore, the type of school, family financial state and the knowledge of EI indirectly influence clinical ability through their impact on "managing emotions" and "facilitating thought". Conclusions EI is essential to enhancing the clinical ability of nursing students. EI training should focus on facilitating thought and managing emotions. It is also necessary for educators to consider the context of nursing students and the characteristics of schools.